TOPoS: VI. The metal-weak tail of the metallicity distribution functions of the Milky Way and the Gaia-Sausage-Enceladus structure (Corrigendum) - Bonifacio, Piercarlo; Monaco, L.; Salvadori, S.; Caffau, E.; Spite, M.; Sbordone, L.; Spite, F.; Ludwig, Hans-Günter; Matteo, P. Di; Haywood, M.; François, P.; Koch-Hansen, Andreas; et al. (Astronomy and astrophysics, 2022)
We realised that there was a mistake in the code that computed parameters for the photometric data sample. The effective temperature was not computed according to the formula in footnote 3. As a consequence the surface gravity and metallicity were also computed incorrectly. We also realised that almost 50% of the lines in the table were duplicated...